DEVELOPING STUDENTSâ READING COMPREHENSION SKILLS THROUGH âKNOW, WANT TO KNOW AND LEARNTâ (KWL) STRATEGY - Utami, Lanjar (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
The objective of the research is to explain the implementation of KWL strategy in Englishreading class and the studentsâ responses towards it. The research was carried out at MANKaranganyar Central Java, from January to May 2016 employing a Classroom Actionresearch (CAR). The subject of the research is thirty students of MAN Karanganyar, twelfthgrade. The data were obtained from several techniques including test, observation, in-depthinterview, questionnaires and document analysis. The researcher applied a descriptivestatistics to analyze the quantitative data and constant comparative method to analyze thequalitative ones. The findings reveal that KWL strategy can develop the studentsâ readingcomprehension skills in finding the main idea, detailed information, inference, wordmeaning, and references. This strategy also helps teachers to get students to be more activeto participate in the process of learning, expanding knowledge, learning their needs andinterests, and activating their background knowledge. It implies that KWL strategy is veryuseful for developing studentsâ reading comprehension skills. Therefore, it is recommendedthe English teachers to apply KWL strategy in teaching reading comprehension.Keywords: Reading Comprehension, KWL, CAR